(untitled) (Sains Humanika, 2017)
Identification of students learning approaches and its characteristics that contribute to learning success are so important in achieving learning outcomes. A previous study has shown that most of the students use more of surface learning approach instead of deep learning approach in their studies. The study uses a questionnaire, R-SPQ-2F to evaluate students’ surface and deep learning approach. This paper will present findings from a study that was carried out to compare the effect of using cooperative learning and the traditional method among students in Industrial Mechatronics Engineering Technology Program at MARA High Skill College Balik Pulau, Penang, Malaysia. The aim is to investigate the effectiveness of each method. Using a quantitative approach, two groups of students, one group from each respective teaching method, were studied. Analysis of the findings found that using cooperative learning has a more positive effect when compared to the traditional learning.